A prospective surveillance study of inhibitor development in haemophilia A patients following a population switch to a third‐generation B‐domain‐deleted recombinant factor VIII. Issue 2 (1st February 2018) - Dubé, E.; Bonnefoy, A.; Merlen, C.; Castilloux, J.‐F.; Cloutier, S.; Demers, C.; Sabapathy, C. A.; St‐Louis, J.; Vezina, C.; Warner, M.; Rivard, G.‐É.
Abstract : Introduction: Following a provincial tender, most subjects with haemophilia A in Quebec switched their treatment to a third‐generation recombinant B‐domain‐deleted factor VIII (FVIII). Aim: Our objective was to evaluate the incidence of inhibitor development and FVIII recovery in patients following the switch of factor replacement therapy. Methods: One hundred and thirty‐five subjects were enrolled and tested for FVIII activity and inhibitors every 6 months during 1 year. Subjects with mild haemophilia A or current inhibitors were excluded. Data on demographics, bleeds and FVIII usage were collected. Results: A total of 125 switchers and 10 non‐switchers were enrolled. Most subjects had severe haemophilia A (95.6%) and were on prophylaxis (89.6%). Mean FVIII recovery was similar at 0, 6 and 12 months postswitch. Two switchers developed de novo inhibitors in the 6 months postswitch, one of which was transient. No recurrent inhibitor was observed. A small but significant increase in FVIII usage was observed for adult switchers and the whole cohort of switchers and non‐switchers. There was an increase in the annualized bleeding rate (ABR) for non‐joint bleeds for the whole cohort of switchers. However, no significant differences were observed in ABR for joint bleeds. Conclusion: Our surveillance study shows comparable inhibitor development to similar published studies. A significant increase in FVIII utilization was noted for the whole cohort, switchers and non‐switchers. Lastly, no clinically significant changes were observed in ABR for joint bleeds, but a difference for non‐joint bleed ABRs was observed in switchers.